Epithelial cytokine responses and mucosal cytokine networks - Hedges, Spencer R.; Agace, William W.; Svanborg, Catharina (Trends in Microbiology, 1995)
Localized at the border between the external environment and the internal tissue, epithelial cells are exposed to stimulants from two directions. Microorganisms in the lumen can activate the transcription of cytokine mRNA and cytokine secretion, and cytokines in the mucosal environment can modify endogenous and microbially induced epithelial cytokine responses. Epithelial cells thus actively participate in mucosal immunity and inflammation.